EVALUATION OF CRACKERS WITH CEREAL FIBER AS A FUNCTIONAL FOOD - ROMÁN M., María O.; VALENCIA G., Francia E. (Vitae, 2009)
The consumption of dietary fiber has been associated with functional food properties which improves people’s intestinal health. It also contributes towards the prevention of colon cancer, cardiovascular diseases, and weight control. The following study intends to evaluate the functional effects of the consumption of crackers elaborated with an addition of a mixture of cereal fiber on a voluntary control group and an experimental group, which daily consumed 100 grams of crackers during 10 days and provides daily information on side effects and digestive product tolerance. There will also be microbiological recounts, volatile fatty acids quantification (AGV´s:, acetic, propionic, butyric), and pH feces samples (MF), and a lipid profile on day 0 and 11. Cracker consumption presents positive tendencies towards the volunteer’s bowel movement.